On the Effects of Reactive Oxygen Species and Nitric Oxide on Red Blood Cell Deformability - Diederich, Lukas; Suvorava, Tatsiana; Sansone, Roberto; Keller, T. C. Stevenson; Barbarino, Frederik; Sutton, Thomas R.; Kramer, Christian M.; Lückstädt, Wiebke; Isakson, Brant E.; Gohlke, Holger; Feelisch, Martin; Kelm, Malte; et al. (Frontiers in Physiology, 2018)
The main function of red blood cells (RBCs) is the transport of respiratory gases along the vascular tree. To fulfill their task, RBCs are able to elastically deform in response to mechanical forces and, pass through the narrow vessels of the microcirculation. Decreased RBC deformability was observed in pathological conditions linked to increased oxidative stress or decreased nitric oxide (NO) bioavailability, like hypertension. Treatments with oxidants and with NO were shown to affect RBC deformability ex vivo, but the mechanisms underpinning these effects are unknown. In this study we investigate whether changes in intracellular redox status/oxidative stress or nitrosation reactions induced by reactive oxygen species (ROS) or NO may affect RBC deformability. In a case-control study comparing RBCs from healthy and hypertensive participants, we found that RBC deformability was decreased, and levels of ROS were increased in RBCs from hypertensive patients as compared to RBCs from aged-matched healthy controls, while NO levels in RBCs were not significantly different. To study the effects of oxidants on RBC redox state and deformability, RBCs from healthy volunteers were treated with increasing concentrations of tert-butylhydroperoxide (t-BuOOH). We found that high concentrations of t-BuOOH (≥ 1 mM) significantly decreased the GSH/GSSG ratio in RBCs, decreased RBC deformability and increased blood bulk viscosity. Moreover, RBCs from Nrf2 knockout (KO) mice, a strain genetically deficient in a number of antioxidant/reducing enzymes, were more susceptible to t-BuOOH-induced impairment in RBC deformability as compared to wild type (WT) mice. To study the role of NO in RBC deformability we treated RBC suspensions from human volunteers with NO donors and nitrosothiols, and analyzed deformability of RBCs from mice lacking the endothelial NO synthase (eNOS). We found that NO donors induced S-nitrosation of the cytoskeletal protein spectrin, but did not affect human RBC deformability or blood bulk viscosity; moreover, under oxidatively unstressed conditions RBCs from eNOS KO mice showed fully preserved RBC deformability as compared to WT mice. Pre-treatment of human RBCs with nitrosothiols rescued t-BuOOH-mediated loss of RBC deformability. These findings suggest that NO does not affect RBC deformability per se, but preserves RBC deformability in conditions of oxidative stress.